Relativistic fluid dynamics - C.I.M.E. Summer School Bressanone, Italy) (1970; Cattaneo, C. (Heidelberg, Germany Springer Berlin, 2011)
m Mau Quam: Problèmes mathématiques en hydrodynamique relativiste.- A. Lichnerowicz: Ondes de choc, ondes infinitésimales et rayons en hydrodynamique et magnétohydrodynamique relativistes.- A.H. Taub: Variational principles in general relativity.- J. Ehlers: General relativistic kinetic theory of gases.- K. Marathe: Abstract Minkowski spaces as fibre bundles.- G. Boillat: Sur la propagation de la chaleur en rel
Pham Mau Quam: Problèmes mathématiques en hydrodynamique relativiste -- A. Lichnerowicz: Ondes de choc, ondes infinitésimales et rayons en hydrodynamique et magnétohydrodynamique relativistes -- A.H. Taub: Variational principles in general relativity -- J. Ehlers: General relativistic kinetic theory of gases -- K. Marathe: Abstract Minkowski spaces as fibre bundles -- G. Boillat: Sur la propagation de la chaleur en relativi
Keywords: Relativistic fluid dynamics